The cross-cultural adaptation and psychometric validation of the MSSS-88 for use in Italian patients with multiple sclerosis. Issue 4 (13th February 2019) - Ottonello, Marcella; Pellicciari, Leonardo; Centonze, Diego; Foti, Calogero; Pistarini, Caterina; Albensi, Caterina; Giordano, Andrea
Abstract: Purpose: To cross-culturally translate the Multiple Sclerosis Spasticity Scale into Italian and to evaluate its psychometric properties in patients with multiple sclerosis. Methods: The Italian version of Multiple Sclerosis Spasticity Scale was developed in accordance with international standards and subsequently administered to 232 Italian adults with multiple sclerosis. The following psychometric properties were analyzed: internal consistency through Cronbach's α and item-to-total correlation, dimensionality with factor analysis, and convergent and criterion validity through hypotheses-testing, comparing the Multiple Sclerosis Spasticity Scale with other outcome measures (Fatigue Severity Scale, Multiple Sclerosis Quality of Life, Modified Ashworth Scale, Barthel Index, and Expanded Disability Status Scale) and analyzing related constructs. Finally, we correlated the MSSS-88 subscales with each other. Results: The final Multiple Sclerosis Spasticity Scale version was well-understood by all subjects. The internal consistency was good (Cronbach's α ≥0.90). Factor analysis revealed that each subscale was unidimensional. Convergent and criterion validity were supported by acceptable correlations with other disease-specific questionnaires, according to the a priori expectations. Conclusions: The final Italian Multiple Sclerosis Spasticity Scale version showed robust psychometric properties. Therefore, it can be recommended as an assessment tool for clinical and research use to evaluate spasticity in Italian patients with multiple sclerosis. Implications for rehabilitation: The Multiple Sclerosis Spasticity Scale was developed to measure patients' perception of the impact of spasticity on life of subjects with multiple sclerosis. In a sample of Italian subjects with multiple sclerosis, the Multiple Sclerosis Spasticity Scale revealed good internal consistency and convergent and criterion validity. Factor analysis demonstrated that each subscale was unidimensional. Each subscale can be used to assess the impact of spasticity in Italian patients with multiple sclerosis.